Visible-light driven photo-catalytic performance of novel composite of TiO2 and fluorinated hexagonal boron nitride nanosheets. Issue 7 (1st April 2021) - Ahmad, Aqrab ul; Abbas, Akmal; Ali, Sajid; e-alam, M.Fakhar; Farooq, Zahid; Abbas, Qasim; Ahmad, Munir; Farid, Amjad; Muhammad afzal, Amir; Umair Arshad, Hafiz Muhammad; Javid, Muhammad; Iqbal, Muzammil
Abstract: This article presents a novel synthesis of fluorinated hexagonal boron nitride (F-BN)/Titanium di-oxide (TiO2 ) hybrid nano-composite by sol-gel method. The prepared nano-composite has shown remarkable photo-catalytic activity under visible light illumination. Our results revealed a strong electrostatic coupling between TiO2 nanoparticles, while the reduced band gap of F-BN makes F-BN/TiO2 highly responsive to visible light. It is also observed that the hybridization of F-BN (with TiO2 ) not only increases the surface absorption but also enhances the electron–hole separation efficiency. The reduced charge carriers' recombination rate of TiO2 nanoparticles leads to visible light driven photo-catalytic activity. Furthermore, the proposed nanocomposite display an excellent cycling stability for up to 5 cycles. Our results would motivate the applications of F-BN/metal oxide nanostructures in multidisciplinary fields especially in water splitting and photo-catalysis.